A Microscopic and Biomarker Evaluation of Embolic Filter Debris Collected During Carotid Artery Stenting. (April 2016) - Yang, Mark; Yu, Yan; Walsh, William R.; Yang, Jia-Lin; Baker, Luke; Lennox, Andrew F.; Crowe, Philip J.; Varcoe, Ramon L.
Purpose: To evaluate and characterize debris retrieved from the cerebral embolic protection devices (EPDs) used during carotid artery stenting (CAS) and compare debris size, volume, tissue types, cellular composition, and protein biomarker expression in symptomatic and asymptomatic patients.Methods: Distal protection filters were retrieved from 22 consecutive patients (mean age 71.6 years, range 52–85; 16 men) undergoing elective CAS between July 2012 and February 2014 for >70% internal carotid artery stenosis (mean 85.4%±10.3%). Six patients were symptomatic. The debris within each EPD was visually characterized using stereomicroscopy and then processed for histology and immunohistochemistry. Biomarkers were immunohistochemically measured to evaluate plaque stability [matrix metalloproteinase-9 (MMP-9)], inflammation [glycoprotein CD68 and interleukin-6 (IL-6)], or phenotype [smooth muscle (SM)-actin and type IV collagen]. The immunohistochemical results were measured using semiquantitative grading criteria based on both staining intensity and distribution in the samples.Results: Macroscopic debris was visible in 5/22 EPDs; 3 of the 5 filters came from symptomatic patients. Microscopic debris was detected in all filters and ranged in size from 0.01 to 8.57 mm 2 . Debris consisted of calcified, fibrous, and necrotic tissue, as well as fibrin and foam cells with no significant difference between the symptomatic and asymptomatic groups. There was no association between the degree or type of embolic material and stenosis severity, carotid tortuosity, calcium grade, soft plaque, or arch type. Symptomatic patients had a larger volume of debris (8.24 vs 0.58 mm 3, p<0.01), mean particle size (1.30 vs 0.32 mm 2, p<0.001), and expression of biomarkers IL-6 (2.17 vs 0.81, p<0.05), CD68 (2.00 vs 0.38, p<0.01), SM-actin (1.00 vs 0.25, p=0.055), type IV collagen (1.17 vs 0.25, p=0.082), and MMP-9 (1.00 vs 0.06, p<0.05).Conclusion: Histological analysis revealed particulate embolization in all EPDs used during CAS. Symptomatic patients had a larger volume of embolic debris, mean particle size, and the biomarkers associated with inflammation, necrotic core, and diminished fibrous cap.